RESTORASI CITRA MENGGUNAKAN JARINGAN SARAF TIRUAN (HOPFIELD) - Silfia Rifka (Elektron : Jurnal Ilmiah, 2009)
The final goal of restoration is image improvement. In general, restoration to degradation modeling and implementation of invers process to get real image. Hopefield method in neural network restoration of image is done by parameters approximation in neural network modeling and reconstruction of degradation image to get real image. In this paper, this method is used image restoration which combines with Gaussian Blur, Uniform Blur and Gaussian Noise. The restoration process using this method take place really fast and suitable to defects restoration of recorder device which recognize the cause of defects and high process speed is needed.